Effects of large-scale Sargassum fusiforme culture on phytoplankton community structure and water quality - Zhang, Yurong; Xu, Dongdong; Li, Tiejun; Qiao, Ling; Xu, Nianjun (Frontiers in Marine Science, 2022)
The large-scale cultivation of S. fusiforme was hypothesized to effectively improve water quality and environmental characteristics. Specifically, such cultivation could promote habitat restoration effects by increasing DO and pH levels in addition to decreasing nitrogen and phosphorus levels within cultivation area waters. Phytoplankton diversity could also reflect the quality and health of waters. This study explored the effects of large-scale cultivation of Sargassum fusiforme on the biodiversity and the ecosystem of a phytoplankton community in the coastal waters of Dongtou island, China. S. fusiforme cultivation increased DO and pH values within the area but decreased N contents of the cultivation area waters. A total of 75 phytoplankton species were identified based on morphological identification, while a parallel survey of phytoplankton communities using high-throughput cultivation-independent sequencing identified 601 phytoplankton OTUs. Large scale cultivation of S. fusiforme was associated with increased phytoplankton diversity as reflected by multiple alpha and beta diversity metrics. These data suggested that S. fusiforme cultivation could affect phytoplankton community structure when the S. fusiforme biomass reached maximum levels. Redundancy analysis (RDA) indicated that S. fusiforme played an important role in controlling the dynamics of phytoplankton communities in coastal ecosystems. Thus, the results suggested that S. fusiforme cultivation could enhance phytoplankton community biodiversity. Overall, this study demonstrated that large-scale cultivation of S. fusiforme in coastal regions was an effective approach for mitigating environmental problems in marine ecosystems.